2022
DOI: 10.1111/1365-2745.13976
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing from unoccupied aerial systems: Opportunities to enhance Arctic plant ecology in a changing climate

Abstract: The Arctic is warming at a faster rate than any other biome on Earth, resulting in widespread changes in vegetation composition, structure and function that have important feedbacks to the global climate system. The heterogeneous nature of arctic landscapes creates challenges for monitoring and improving understanding of these ecosystems, as current efforts typically rely on ground, airborne or satellite‐based observations that are limited in space, time or pixel resolution. The use of remote sensing instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 220 publications
(405 reference statements)
0
5
0
Order By: Relevance
“…Using these PiCAMs, we were able to obtain robust time‐series observations of plant growth in autumn, as well as in spring (Figure 5) a shoulder season that is essential for phenology studies (Myers‐Smith et al., 2020). In addition, our compact, lightweight design significantly simplified the installation, making it possible to deploy a large number (26 in our case) of PiCAMs with minimal cost, essential for monitoring the heterogeneous plant phenology of Arctic landscapes (Yang et al., 2022).…”
Section: Discussion and Future Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using these PiCAMs, we were able to obtain robust time‐series observations of plant growth in autumn, as well as in spring (Figure 5) a shoulder season that is essential for phenology studies (Myers‐Smith et al., 2020). In addition, our compact, lightweight design significantly simplified the installation, making it possible to deploy a large number (26 in our case) of PiCAMs with minimal cost, essential for monitoring the heterogeneous plant phenology of Arctic landscapes (Yang et al., 2022).…”
Section: Discussion and Future Improvementsmentioning
confidence: 99%
“…The time‐series images and GCC data used to support this study can be found at Yang, McMahon, Anderson, Hantson, and Serbin (2023). The data set that included images collected by all 26 PiCAMs between August 2021 and July 2022 is available at Yang, McMahon, Anderson, Hantson, Ely, and Serbin (2023). A complete guide on how to assemble, programme and operate a PiCAM can also be found on GitHub (https://github.com/TESTgroup-BNL/PiCam).…”
Section: Peer Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, heatwaves and droughts may weaken this cooling effect and create a sensible heat flux dominance, further intensifying the heatwave, such as during the 2010 heatwave and drought in western Siberia (Hauser et al 2016). Most studies linking land surface energy budgets with soil moisture relied on a few point measurements from flux chambers or towers (Marchand et al 2006, Thunberg et al 2021, Zona et al 2022 Yet, we have limited knowledge of how the effect of drought on land surface cooling varies across space at landscape and regional scales in the tundra biome (Farella et al 2022, Yang et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…These factors make the spatial monitoring of community changes via traditional methods challenging (Convey et al., 2014). unoccupied aerial systems (UAS) or drones are a commonly used tool for monitoring natural vegetation and have been demonstrated to be suitable for mapping the extent and biophysical properties of moss beds in Antarctica (Bollard et al., 2022; Bollard‐Breen et al., 2014; Lucieer et al., 2014; Malenovsky et al., 2013; Malenovský et al., 2017; Turner et al., 2014, 2018) and other similar vegetation communities in the Arctic (Nelson et al., 2022; Yang et al., 2022). A benefit of using UAS remote sensing to study Antarctic moss beds is the ability to capture biophysical and biochemical moss traits at ultrahigh spatial resolution (<5 cm/pixel) over entire catchment areas.…”
Section: Introductionmentioning
confidence: 99%